Hola. ¡Adiós! - Montijo, Rhode (Montijo, Rhode. Skeletown (Series), 2025)
"In a humorous exploration of the words "hola" and "adiós," a skeleton-like character inspired by Día de los Muertos learns to fly a kite but causes trouble wherever he goes"--